Exercising a general partner’s rights in a limited partnership by its commercial proxy. Scientific commentary on the decision of the Supreme Court of 16 june 2016, V CZ 26/16 - Zbrojewski, Adrian (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The commentary refers to the Supreme Court’s judgment allowing a commercial proxy of a general partner, which is a legal person, to represent the limited partnership even if its management board is not fully appointed. Having agreed with the aforementioned statement, the author criticizes the reasons for the judgment. In particular, the commentary points out that Supreme Court did not make an analysis of the concept of ‘acts connected with running the enterprise’ which determines a scope of empowerment of the commercial proxy. As a consequence, the author tries to define the above-mentioned concept, which eventually leads the author to the conviction that the scope of commercial power of attorney comprises the exercise of the general partner’s rights in the limited partnership. The author also considers the issue of the invalidity of proceedings in terms of defectiveness of litigants’ representation.